PENGARUH KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR MATA PELAJARAN PAI PESERTA DIDIK DI SMP MA’ARIFiKOTAiBATU - fahrudin hardiansyah; Ika Ratih Sulistiani; Indhra Musthofa (VICRATINA, 2021)
A reportifromithe National Center for Clinical Infant Programs states that success in school is not only predicted by a student's fact collection or reading ability from an early age, but by emotional and social measures. The purpose of this study was to describe emotional intelligence, describe learning achievement in PAI subjects and determine the effect of emotional intelligence on PAI learning achievement for students of classVII-A at SMP Ma'arif Kota Batu. The approach used is a quantitative approach. The hypothesis testing method uses the Wilcoxon Sign Test Ranked. Questionnaire and documentation methods were used as instruments to collect research data. The results of the study stated that the level of emotional intelligence of class VII-A students was in the medium category and the level of PAI learning achievement was also in thei medium category.KataiKunci:iKecerdasaniEmosional,iPrestasiiBelajar,iPAI